Citation Analysis Disparity Between Sub-Areas of Brazilian Computer Science - Druszcz, Fernando F.; Vignatti, André L. (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2024)
Among the various ways of evaluating scientific production, there is a tendency to use metrics based on the number of citations. Apart from obvious problems, this takes on a new dimension when it is used to compare areas and sub-areas, specially from unfair assessments if submitted to the same evaluation committee. In this work, we examine various sub-areas of Computer Science using data from the Brazilian community. Our findings reveal a disparity in citations among these sub-areas, which may lead to issues if they are evaluated using the same criteria for scientific productivity. We demonstrate how the universal fit citation, previously proposed by Radicchi et al., can help mitigated these concerns.